Governance framework for flood disaster in Malaysia: integration of COBIT and Hyogo principles - Maidin, Siti Sarah; Othman, Marini; Yahya, Norzariyah (Journal of Advanced Research in Dynamical and Control Systems, 2019)
-Flood disaster (FD) governance in Malaysia is chaotic and extremely complex in nature. Thus, it gives rise to the need for proper governance to be in place in the form of clear operating procedures, governance structures, activities and information-related needs in FD. This paper aims to address this need by constructing a governance framework for FD governance in Malaysia. Primary data were collected through face-to-face interviews with FD agency officers who were involved directly in flood. Other sources included books, journal articles and government reports. The study constructs the flood governance framework which consists of six critical components: the driving vision and mission; responding disaster agencies; processes layer; knowledge management layer; information base and knowledge base layer; and governance layer. The building blocks for each component are co-related. The findings of the study reveal that a flood governance framework is essential as a comprehensive platform for effective FD cross-agency coordination, information sharing, transparency and decision-making processes. This paper explores the current governance structure in the decision-making process specifically in relation to cross-agency collaboration and information sharing in order to achieve the organizations’ vision and mission. The paper recommends a governance framework for FD by adopting the principles of Control Objective for Information and Related Technologies (COBIT) and the Hyogo Framework for Action